Pengaruh Kompetensi Dan Knowledge Management Terhadap Kinerja Pegawai (Studi Kasus di Universitas Pendidikan Indonesia Kampus Tasikmalaya) - Peri Herdiyana; Apri Budianto; Ferey Herman; S. Nailul Muna Aljamaliah (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The research was conducted with the aim of knowing the effect of Competence and Knowledge Management on Employee Performance at the Indonesian University of Education, Tasikmalaya Campus. The method used is a quantitative descriptive method. The results of the study show that competence has a positive and significant effect on the performance of Administrative Section Employees of the UPI Tasikmalaya Campus. This means that if the competence of employees increases, the performance of the Administrative Section Employees will also increase. Knowledge management has a positive and significant effect on the performance of Administrative Section Employees of the UPI Tasikmalaya Campus. This means that if knowledge management increases, the performance of Administrative Officers will also increase. Competence and knowledge management have a positive and significant effect on the performance of Administrative Section Employees of the UPI Tasikmalaya Campus. This means that if competence and knowledge management increases, the performance of the Administrative Section Employees also increases.